Drivers of caregiver impact in Duchenne muscular dystrophy: a cohort study - Carolyn E. Schwartz; Roland B. Stark; Katrina Borowiec; Bruce D. Rapkin (SpringerOpen, 2022)
Abstract Background In our companion paper, we addressed the interplay between caregiver impact, out-of-pocket expenditures, and Duchenne Muscular Dystrophy (DMD) disability. We found that DMD caregiver impact could be characterized by four Latent Profile Analysis impact profiles: lowest, lower middle, upper middle, and highest impact. The impact on caregivers was often but not always worse with greater out-of-pocket expenditures. Further, while the lowest-, lower-middle, and highest-impact profiles reflected low, moderate and high disability-related caregiver burden, respectively, the upper-middle profile group was quite variable in level of disability across domains. To better understand the four caregiver-impact profiles, we examine how a comprehensive set of psychosocial factors differentiate the four profile groups. Methods Psychosocial factors assessed included demographic characteristics, quality of life (QOL), stress, cognitive appraisal, reserve-building, and general and COVID-specific resilience. Linear modeling examined relationships between impact profiles and psychosocial factors. We used effect size rather than p-value as the criterion for determining relevance of the broad range of characteristics examined. Results Multivariate analyses implicated stress and environmental mastery, appraisal sampling of experience, COVID-specific variables, appraisal standards of comparison, appraisal goals, demographics, appraisal combinatory algorithm, reserve-building, and resilience, in order of prominence (average eta2 = 0.29, 0.29, 0.16, 0.15, 0.09, 0.07, 0.07, 0.06, 0.05, and 0.02, respectively). On the whole, comparisons of highest-versus-lowest impact profiles revealed more and larger differences than comparisons of upper-middle versus lower-middle impact profiles. Life stress, goals, and reserve-building activities had a smaller differentiating effect in the middle groups. Conclusion A more comprehensive 'story' about DMD caregiver impact involves life stress, environmental mastery, COVID-specific variables, and cognitive and behavioral factors. Implications are discussed for coaching interventions to support DMD caregivers.